Negotiation between modernity and local culture in moviegoing practice: A case study of a traditional movie theater in Guangzhou Metropolis. (September 2021) - Lin, Geng; Wu, Hao; Xie, Xiaoru; Fan Yang, Fiona; Lv, Zuyi
As a medium for delivering modernity, movie theaters have faithfully recorded the dialogue between modernity and local daily lives. In contrast to modern movie theaters, traditional cinemas are distinguished by their long history, through which they reflect the changing connotations and social construction of modernity over time. Based on detailed analysis of the historical and social characteristics of Nanguan cinema, a 100-year-old movie theater in Guangzhou, China, we reach the following two conclusions: first, shaped by local traditional culture, the practice of moviegoing localizes modernity with a distinctive grassroots feature that enlivens everyday lives; second, moviegoing at traditional theaters in modern metropolitan areas has further enriched the connotations of modernity by providing a nostalgic experience for audiences.